Estimation of parameters of the special fitness of young ski jumpers - Lebedev, G. K. (Vestnik sportivnoj nauki; Sports science bulletin, 2018)
In this article, the authors have investigated the test results of special fitness of young ski jumpers. The authors presented a comparative analysis of the parameters of technical and psychological fitness, coordination abilities, morphological parameters, speed-power qualities of young ski jumpersfor boys and girls. The comparative analysis of the parameters of technical and psychological preparedness, coordination abilities, morphological parameters, speed-strength qualities of young skiers-jumpers of young men and girls is carried out. It was revealed that the indices laid down in the Federal Standard of Sports Training do not allow to evaluate objectively the athlete`s preparedness. A testing technique is proposed using a battery of tests that best characterize the capabilities of the athlete, especially speed-power. The effectiveness of the system for assessing the successive mastery of three levels of the technique of jumping and analysis of the kinematic parameters of the ski jump technique for determining the level of technical preparedness of young skiers.